Institutional shifts and landscape change: the impact of the Período Especial on Cuba's land system architecture. Issue 5 (2nd September 2020) - Stuhlmacher, Michelle; Turner, B.L.; Frazier, Amy E.; Kim, Yushim; Leffel, Jessica
ABSTRACT: Formal institutions, especially policies, play a key role in land system change. Compared to other drivers of change, however, the impact of policies on landscapes is under-addressed in land system science, in part due to difficulties isolating their effect on longitudinal land change. We address this gap by examining land system architecture changes in Cuba brought about by the 1991 collapse of the Soviet Union and the resulting economic crisis: El Período Especial ('Special Period'). Employing a satellite imagery time-series alongside a review of policy documents, we identify statistically significant land system changes linked to the era's institutional shifts. We find that concentrated policy efforts to transform agriculture and protect forests corresponded to considerable changes for agriculture but minimal changes to forests. Some changes resulting from the institutional shifts of the Período Especial became visible in the landscape as soon as a few years, while others took decades to manifest.